Evaluating Dry Eye and Meibomian Gland Dysfunction With Meibography in Patients With Stevens–Johnson Syndrome. Issue 12 (December 2019) - Lekhanont, Kaevalin; Jongkhajornpong, Passara; Sontichai, Vachira; Anothaisintawee, Thunyarat; Nijvipakul, Sarayut
Abstract : Purpose: To investigate ocular surface and meibomian gland characteristics using infrared meibography in patients with Stevens–Johnson syndrome (SJS). Methods: This is a single-center, prospective, noncontrolled, observational study. Thirty-two Thai patients (64 eyes) with SJS for 1 year or longer (1–44 years) were enrolled in the study. All participants underwent a comprehensive ophthalmic examination including slit-lamp biomicroscopy, tear meniscus height, fluorescein tear breakup time, ocular surface fluorescein staining, eyelid morphology, Schirmer 1 test, meibomian gland expressibility, and upper and lower eyelid meibography using a noncontact infrared meibograph mounted on a slit-lamp biomicroscope. Results: The mean age was 42.2 ± 17.7 years (range, 4–68 years). Twenty-nine patients (90.6%) had a history of severe ocular complications in the acute stage of the disease. Medications were the most common cause of SJS (93.8%). Meibum quality could not be assessed in 23 patients (71.9%) due to no glands expressible. Partial or complete loss of the meibomian glands in either the upper or lower eyelid was found in all patients. The degree of meibomian gland dropout significantly correlated with tear breakup time ( P < 0.001), meibum quality ( P < 0.001), meibum expressibility ( P < 0.001), ocular surface staining ( P < 0.001), and presence of long-term ocular sequelae including symblepharon ( P = 0.027) and limbal stem cell deficiency ( P = 0.003). Conclusions: SJS is associated with obstructive meibomian gland dysfunction. The severity of meibomian gland dropout has a relationship with abnormal dry eye tests, subjective meibomian gland evaluation, and other ocular sequelae of SJS.